Ethnic identity as an expression of the socialization of a personality - Danyliuk, Ivan (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2017)
The article is a theoretical analysis of the problem of ethnic identity and its basic mechanisms. The factors of formation of ethnic identity are explained. The possibilities of ethnic socialization of a personality are reviewed. The features of ethnic identity expression as an important component of socialization and as a leading factor of further development of the personality, its productive functioning in society are provided.